A novel splice-site mutation in ALS establishes the diagnosis of juvenile amyotrophic lateral sclerosis in a family with early onset anarthria and generalized dystonias - Siddiqi S. (Public Library of Science (PLoS), 2018)
10.1371/journal.pone.0113258